Effective Technological Delivery in Nigerian Polytechnics:Need for Academic Manpower Development Policy - Adeyemi, J. K.; Uko-Aviomoh, E. E. (Education Policy Analysis Archives, 2004)
Technical education, especially as provided in the Nigerian polytechnics, leads to the acquisition of practical and applied skills as well as basic scientific knowledge. The production function of the polytechnics in terms of producing quality middle-level manpower through effective teaching delivery depends largely on the quantity and quality of teachers available. However, teacher adequacy is a function of many factors, which include funding, student enrollment overtime, and staff turnover. This article, however, revealed a mismatch between enrollment and available teachers, with huge staff shortfall over the years when the student enrollment was matched with the available teachers, using the ideal teacher-student ratios. Student and teacher projections were carried out based on five-percent annual increase and average teacher-student ratio of 1:12, so as to meet the vision 2010 target year set by the Nigerian government for total development. The projection showed that the polytechnics would require a large additional number of teachers. An all-inclusive funding approach for the polytechnics was recommended so as to increase their financial status, which would allow for improved facilities, workshops, equipment and also improved conditions of service of teachers. We believe that if this was done, more teachers would be attracted from across the world, those who left would return, and new and younger ones will be encouraged to join the teaching force. Such development would to a great extent meet and sustain the anticipated growth for the target year.